Exploiting Data Compression to Mitigate Aging in GPU Register Files - Candel, Francisco; Valero, Alejandro; Petit, Salvador; Suárez-Gracia, Darío; Sahuquillo, Julio (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2017: Anais do XXIX International Symposium on Computer Architecture and High Performance Computing, 2017)
Nowadays, GPUs sit at the forefront of highperformance computing thanks to their massive computational capabilities. Internally, thousands of functional units, architected to be fed by large register files, fuel such a performance.At nanometer technologies, the SRAM cells that implement register files suffer the Negative Bias Temperature Instability (NBTI) effect, which degrades the transistor threshold voltage Vth and, in turn, can make cells faulty unreliable when they hold the same logic value for long periods of time.Fortunately, the GPU single-thread multiple-data execution model writes data in recognizable patterns. This work proposes mechanisms to detect those patterns, and to compress and shuffle the data, so that compressed register file entries can be safely powered off, mitigating NBTI aging.Experimental results show that a conventional GPU register file experiences the worst case for NBTI, since maintains cells with a single logic value during the entire application execution (i.e., a 100% 0 and 1 duty cycle distributions). On average, the proposal reduces these distributions by 61% and 72%, respectively, which translates into Vth degradation savings by 57% and 64%, respectively.